2020
DOI: 10.3390/molecules25194521
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles from Pomegranate (Punica granatum) Extracts and Characterization of Their Antibacterial Activity

Abstract: This study assessed the antimicrobial efficacy of synthesized zinc oxide nanoparticles produced using aqueous extracts of pomegranate leaves and flowers designated ZnO-NPs-PL, ZnO-NPs-PF. In the study, oxides of zinc were successfully employed to fabricate nanoparticles using extracts from leaves and flowers of pomegranate (Punica granatum). The nanoparticles obtained were characterized spectroscopically. X-ray diffractive analysis (XRD) revealed the elemental components and nature of the synthesized particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 60 publications
7
53
0
Order By: Relevance
“…Tang et al ( 2016 ) indicated that ZnO-NPs increased the white blood cell counts mainly granulocyte and neutrophil and decreased the lymphocyte count which reflects the inflammatory reaction and the immune dysfunction. Generally, the increased level of MDA, NO, TNF-α, AFP, and CEA and the decrease in TAC, SOD, and CAT suggested that the toxicity of ZnO-NPs is mainly via the production of reactive oxygen species (ROS) and inflammation (Ifeanyichukwu et al 2020 ; Tian et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al ( 2016 ) indicated that ZnO-NPs increased the white blood cell counts mainly granulocyte and neutrophil and decreased the lymphocyte count which reflects the inflammatory reaction and the immune dysfunction. Generally, the increased level of MDA, NO, TNF-α, AFP, and CEA and the decrease in TAC, SOD, and CAT suggested that the toxicity of ZnO-NPs is mainly via the production of reactive oxygen species (ROS) and inflammation (Ifeanyichukwu et al 2020 ; Tian et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spectrophotometer: (Figure 1) showed an absorption peak at 261 nm which indicates the successful biosynthesis of amygdalin ZnO NPs. Researcher of (Ifeanyichukwu, et al 2020) reported that combined vibration of electrons of the biosynthesized nanoparticles indicate with the light wave. And this due to the surface Plasmon resonance (SPR), which is a distinguishing property of the nanoparticles (Thamer, N.A.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not possible to exclude that the effects observed in our study could be due to the presence of other substances such as zinc oxide, cornstarch, arginine, allantoin, or magnesium oxide. Indeed, some of these substances have been recently associated to antibacterial activities [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%